Microcrystalline graphite intercalation compound, expanded microcrystalline graphite and application

The microcrystalline graphite interlayer compound was prepared by high-temperature mechanical force chemistry method, and expanded microcrystalline graphite was obtained through high-temperature expansion treatment, which solved the instability and environmental protection problems of the preparation method in the prior art. It realizes efficient and environmentally friendly preparation of electromagnetic wave absorbing materials.

CN119490184APending Publication Date: 2025-02-21ARMOR ACADEMY OF CHINESE PEOPLES LIBERATION ARMY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411661152.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing methods for preparing inter-graphite compound in the production of low yield, long reaction time, high reaction temperature and unstable product structure. The strong oxidant used will release harmful gases, affecting the performance and environmental protection of the product.

Method used

Using high-temperature mechanical force chemistry method, N-chlorosuccinimide, anhydrous aluminum chloride and microcrystalline graphite mixed ball milling, using anhydrous AlCl3 as an intercalation agent to replace the acidic strong oxidizing agent to prepare the microcrystalline graphite layer. Compounds are used to obtain expanded microcrystalline graphite by high temperature puffing treatment.

Benefits of technology

The environmentally friendly preparation of microcrystalline graphite interlayer compounds is achieved, and large-scale production can be achieved, the production of harmful gases is reduced, and the corrosion resistance and electromagnetic wave absorption performance of the product are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490184A_ABST
    Figure CN119490184A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a microcrystalline graphite intercalation compound, which comprises the following steps: mixing and ball-milling N-chlorosuccinimide, anhydrous aluminum chloride and microcrystalline graphite, washing and drying to obtain the microcrystalline graphite intercalation compound. Anhydrous AlCl3 is used as an intercalator to replace an acidic strong oxidant, so that the requirements of some fields on corrosion resistance of products are met, and the generation of harmful gas can be effectively reduced. The xAlCl3-yMGIC powder is prepared under relatively mild conditions by using microcrystalline graphite as an acceptor carbon source and N-chlorosuccinimide as a chlorinating agent and adopting a high-temperature mechanochemical method. And then the prepared xAlCl3-yMGIC powder is used as a raw material to prepare expanded microcrystalline graphite (EMG) which can be used for preparing an electromagnetic wave absorbing / shielding material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of graphite, and in particular relates to a microcrystalline graphite intercalation compound and expanded microcrystalline graphite and applications thereof. Background Art

[0002] Oxides such as SiO2, Al2O3, Fe2O3, CaO, MgO, TiO2, K2O, Na2O, and MnO2 in natural graphite (MG) are all components that are beneficial to improving the absorbing performance, that is, about 97% of the components in natural MG can be used to prepare high-performance absorbing materials, and only about 3% of volatiles and water are not beneficial to improving the absorbing performance. Therefore, it is possible to consider using appropriate methods to remove volatiles and water in natural MG as much as possible, while retaining the trace oxide components inside it, which not only avoids the waste of resources and energy caused by excessive purification, but also applies natural MG to the preparation of high-performance absorbing materials, thereby improving its utilization rate and added value.

[0003] The preparation methods of graphite intercalation compounds (GICs) mainly include gas diffusion method, solid mixing method, liquid phase chemical oxidation method and molten salt electrochemical method. Although the above methods are relatively mature, they still have limitations such as low yield, long reaction time, high reaction temperature and unstable product structure. Chemical oxidation method is the most mature and widely used preparation method. This process usually uses strong oxidants (such as concentrated sulfuric acid, concentrated nitric acid and potassium permanganate) to insert into the acceptor graphite. However, these strong oxidants will release harmful gases such as sulfur dioxide and nitrogen oxides into the air during use, and produce corrosive residues, which will affect the performance of the product and shorten its service life. The trend of sustainable development has put forward higher requirements on the environmental protection and safety of materials. Therefore, it is urgent to find an environmentally friendly preparation method that can achieve large-scale industrial production. Summary of the invention

[0004] In view of this, the technical problem to be solved by the present invention is to provide a microcrystalline graphite intercalation compound and expanded microcrystalline graphite and their applications. The preparation methods of the microcrystalline graphite intercalation compound and expanded microcrystalline graphite provided by the present invention are environmentally friendly and can achieve mass production.

[0005] The present invention provides a method for preparing a microcrystalline graphite intercalation compound, comprising the following steps:

[0006] The microcrystalline graphite intercalation compound is obtained by mixing N-chlorosuccinimide, anhydrous aluminum chloride and microcrystalline graphite, ball milling, washing and drying.

[0007] Preferably, the mass ratio of the anhydrous aluminum chloride to the microcrystalline graphite is 3:1 to 1:3.

[0008] Preferably, the usage amount of the N-chlorosuccinimide is 10 wt % to 30 wt % of the total amount of the N-chlorosuccinimide, anhydrous aluminum chloride and microcrystalline graphite.

[0009] Preferably, the temperature of the mixed ball milling is 200-400° C., the time is 5-12 hours, and the ball-to-material ratio is 5-20:1.

[0010] Preferably, the washing comprises the following steps:

[0011] The ball-milled reaction product was pickled with a hydrochloric acid solution and then washed with deionized water and anhydrous ethanol.

[0012] The present invention also provides a microcrystalline graphite intercalation compound prepared by the above preparation method.

[0013] The present invention also provides an expanded microcrystalline graphite, which is obtained by subjecting the above-mentioned microcrystalline graphite intercalation compound to high-temperature expansion treatment.

[0014] Preferably, the temperature of the high temperature puffing treatment is 800-1000° C., and the time is 40-100 seconds.

[0015] The present invention also provides an application of the above-mentioned microcrystalline graphite intercalation compound in the preparation of electromagnetic wave absorbing or shielding materials.

[0016] The present invention also provides an application of the expanded microcrystalline graphite in preparing electromagnetic wave absorbing or shielding materials.

[0017] Compared with the prior art, the present invention provides a method for preparing a microcrystalline graphite intercalation compound, comprising the following steps: mixing N-chlorosuccinimide, anhydrous aluminum chloride and microcrystalline graphite, ball-milling, washing and drying to obtain a microcrystalline graphite intercalation compound. The present invention uses anhydrous AlCl3 as an intercalation agent to replace the acidic strong oxidant, which meets the requirements for product corrosion resistance in certain fields and can effectively reduce the generation of harmful gases. Using microcrystalline graphite as an acceptor carbon source and N-chlorosuccinimide as a chlorinating agent, a high-temperature mechanochemical method is used to prepare xAlCl3-yMGIC powder under relatively mild conditions. Subsequently, the prepared xAlCl3-yMGIC powder is used as a raw material to prepare expanded microcrystalline graphite (EMG), which can be used to prepare electromagnetic wave absorption / shielding materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Schematic diagram of the preparation process of xAlCl3-yMGIC and EMG powders;

[0019] Figure 2 XRD patterns of MG and xAlCl3-yMGIC powders;

[0020] Figure 3 FT-IR spectra of MG and xAlCl3-yMGIC powders;

[0021] Figure 4 N2 adsorption-desorption isotherms of MG and xAlCl3-yMGIC powders;

[0022] Figure 5 BET parameter distribution curves of MG and xAlCl3-yMGIC powders;

[0023] Figure 6 is the pore size distribution diagram of MG and xAlCl3-yMGIC powders;

[0024] Figure 7 Raman images of MG and xAlCl3-yMGIC powders;

[0025] Figure 8 The XPS total spectra and high-resolution spectra of the corresponding elements of MG and AlCl3-MGIC powders;

[0026] Fig. 9 FE-SEM morphology, EDS elemental distribution, TEM and HR-TEM images of MG and xAlCl3-yMGIC powders;

[0027] Fig.10 The relationship curve between the electromagnetic parameters and frequency of MG and xAlCl3-yMGIC powders;

[0028] Fig.11 3D R of MG and xAlCl3-yMGIC powders L Figure and R in a specific thickness range L The frequency dependence curve of

[0029] Fig.12 Cole-Cole curves of MG and xAlCl3-yMGIC powders;

[0030] Fig.13 C0-f curves of MG and xAlCl3-yMGIC powders;

[0031] Fig.14 The attenuation coefficient (α) and impedance matching characteristics (Z) of MG and xAlCl3-yMGIC powders vary with frequency;

[0032] Fig.15 The mechanism diagram of the preparation process of xAlCl3-yMGIC;

[0033] Fig.16 The electromagnetic wave loss mechanism diagram of xAlCl3-yMGIC powder;

[0034] Fig.17 XRD patterns of MG, AlCl3-MGIC and EMG powders;

[0035] Fig.18 N2 adsorption-desorption isotherms and pore size distribution diagram of EMG powder;

[0036] Fig.19 It is the XPS overall spectrum of EMG and AlCl3-MGIC powder;

[0037] Fig. 20 This is the elemental high-resolution spectrum of C1s and O1s of EMG powder;

[0038] Fig.21 Volume change diagram of equal mass MG, AlCl3-MGIC and EMG powders

[0039] Fig. 22 SEM images of MG, xAlCl3-yMGIC and EMG powders;

[0040] Fig.23 TEM and HR-TEM morphology images of EMG powder;

[0041] Fig.24 is the relationship between the electromagnetic parameters and frequency of MG, AlCl3-MGIC and EMG powders;

[0042] Fig.25 The three-dimensional R of EMG powder L Graphs and three-dimensional Cole-Cole plots. DETAILED DESCRIPTION

[0043] The present invention provides a method for preparing a microcrystalline graphite intercalation compound, comprising the following steps:

[0044] The microcrystalline graphite intercalation compound is obtained by mixing N-chlorosuccinimide, anhydrous aluminum chloride and microcrystalline graphite, ball milling, washing and drying.

[0045] The present invention firstly mixes N-chlorosuccinimide, anhydrous aluminum chloride and microcrystalline graphite for ball milling. The mass ratio of the anhydrous AlCl3 as an intercalation agent to the microcrystalline graphite is 3:1 to 1:3, and can be 3:1, 2:1, 1:1, 1:2, 1:3, or any value between 3:1 and 1:3.

[0046] The N-chlorosuccinimide as a chlorinating agent accounts for 10wt% to 30wt% of the total amount of the N-chlorosuccinimide, anhydrous aluminum chloride and microcrystalline graphite, and can be 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, or any value between 10wt% and 30wt%.

[0047] In the present invention, the temperature of the mixed ball mill is 200-400°C, which can be 200, 250, 300, 350, 400, or any value between 200 and 400°C; the time is 5-12h, which can be 5, 6, 7, 8, 9, 10, 11, 12, or any value between 5 and 12h; the ball-to-material ratio is 5-20:1, which can be 5:1, 10:1, 15:1, 20:1, or any value between 5 and 20:1.

[0048] After mixing and ball milling, a reaction product is obtained. Then, the reaction product is washed. In the present invention, the washing comprises the following steps:

[0049] The ball-milled reaction product was pickled with a hydrochloric acid solution and then washed with deionized water and anhydrous ethanol.

[0050] Wherein, the hydrochloric acid solution has a concentration of 0.2-0.3 mol·L -1 The concentration of the hydrochloric acid solution may be 0.2, 0.22, 0.24, 0.25, 0.26, 0.28, 0.3, or 0.2-0.3 mol·L -1 The specific pickling process includes adding the ball-milled reaction product into a hydrochloric acid solution and performing pickling with magnetic stirring for 20 to 30 minutes to remove unreacted intercalant AlCl3.

[0051] Then, the acid-washed product was repeatedly washed with deionized water and anhydrous ethanol.

[0052] Finally, the washed reaction product is dried to obtain a microcrystalline graphite intercalation compound (xAlCl3-yMGIC). In xAlCl3-yMGIC, x is 1 to 3 and y is 1 to 3.

[0053] The present invention also provides a microcrystalline graphite intercalation compound prepared by the above preparation method.

[0054] In the present invention, the formation mechanism of xAlCl3-yMGIC powder is as follows:

[0055] The reaction mechanism of xAlCl3-yMGIC powder prepared by high temperature mechanochemical method is as follows Fig.15As shown. When the temperature is higher than the boiling point of the metal chloride, the gaseous metal chloride can enter between the graphite layers in a chlorine atmosphere to form graphite intercalation compounds. AlCl3 is a common metal chloride, which has the lowest boiling point (about 451K) among all metal chlorides. As an environmentally friendly intercalation agent, AlCl3 replaces acidic strong oxidants as intercalation agents, which meets the requirements for product corrosion resistance in certain fields and can effectively reduce the generation of harmful gases. N-chlorosuccinimide (C4H4ClNO2) is a chlorinating agent, which can be pyrolyzed at a certain temperature (388-473K) to release chlorine. In this case, the gaseous AlCl3 will be inserted between the graphite layers to obtain graphite intercalation compounds.

[0056] When the temperature of the reaction system is 523K, the solid phase AlCl3 will smoothly transform into AlCl3 vapor, C4H4ClNO2 will pyrolyze and release chlorine, so that the entire reaction system is in a chlorine atmosphere. At the same time, the presence of mechanical force will open the edge of microcrystalline graphite (MG), which is conducive to the intercalation reaction. As the reaction time increases, more C4H4ClNO2 pyrolyzes and releases chlorine, resulting in an increase in the chlorine partial pressure inside the system. At this time, AlCl3 vapor will be inserted into the graphite layers under the action of chlorine to form GICs. AlCl3 will play a supporting role between the graphite layers, increase the interlayer spacing of graphite, and introduce a certain degree of defects at the edge of the graphite layer.

[0057] In summary, the formation process of xAlCl3-yMGIC powder can be divided into four stages: the gasification of AlCl3 and the pyrolysis of C4H4ClNO2, the activation of gas phase AlCl3 breaking through the energy barrier between MG layers, the diffusion of AlCl3 molecules in the MG carbon atom layer, and the bonding between AlCl3 and graphite carbon atoms. The specific analysis of each stage is as follows:

[0058] (1) Gasification of AlCl3 and pyrolysis of C4H4ClNO2: This stage is the primary condition for the synthesis of xAlCl3-yMGIC powder and is mainly determined by temperature. As long as the temperature conditions are met, the process can be completed quickly.

[0059] (2) Activation stage of gas phase AlCl3 breaking through the energy barrier between MG layers: The interlayer spacing of graphite is about 0.335nm, and the position of a single AlCl3 ligand is about 0.6nm. If AlCl3 molecules want to successfully enter the interlayer spacing of graphite with extremely small interlayer spacing, they must have energy higher than the atomic binding energy between graphite layers. In this reaction system, the energy of AlCl3 molecules mainly comes from the reaction conditions of the system (such as reaction temperature and chlorine partial pressure, etc.). When the temperature of the reaction system remains stable, the gas partial pressure inside the system becomes the main determining factor. As the ball milling time increases, more C4H4ClNO2 will undergo thermal decomposition and release chlorine, and the chlorine partial pressure inside the system will increase, which will give AlCl3 molecules enough energy to overcome the original binding force between graphite layers. With sufficient energy, this process can also be completed in a short time.

[0060] (3) Diffusion stage of AlCl3 molecules in the MG carbon atom layer: To obtain xAlCl3-yMGIC powder with uniform AlCl3 distribution and good performance, sufficient reaction time must be provided. In addition, the size of graphite flakes is also one of the important influencing factors. Small graphite flake diameter can make AlCl3 molecules quickly and evenly distributed between graphite layers. There is a continuous mechanical force in this reaction system, which will refine the graphite flakes and help AlCl3 molecules to be more evenly distributed. This process generally takes a long time.

[0061] (4) Bonding stage between AlCl3 and MG carbon atoms: After the AlCl3 molecule successfully enters the MG layer, charge transfer will occur between the AlCl3 molecule and the MG carbon atom layer, forming certain chemical bonds, thereby forming GICs. In this process, the charge transfer between them starts from the edge of the MG end face. The electron cloud of the carbon atom in the MG interacts with the outer electrons of the Al atom in the AlCl3 molecule, reducing the energy of the system and reaching a steady state. This form of charge transfer is also one of the typical driving forces of the intercalation reaction.

[0062] In the present invention, the xAlCl3-yMGIC powder has certain electromagnetic wave absorption performance, and its possible absorption mechanism is as follows: Fig.16 When the incident electromagnetic wave contacts the xAlCl3-yMGIC powder, part of the electromagnetic wave will be directly reflected back to the free space; part of the electromagnetic wave will directly enter the sample, interact with the xAlCl3-yMGIC powder, and be converted into other forms of energy and attenuated or dissipated; the remaining small part will be emitted after penetrating the absorber and return to the free space.

[0063] Among them, the incident electromagnetic wave entering the absorption layer may cause various losses, mainly including:

[0064] (1) There are a large number of polar functional groups and chemical bonds in xAlCl3-yMGIC powder. Different atoms in these structures can show different attraction and binding abilities to free electrons, thus causing electron pair imbalance. In addition, a large number of defects and vacancies are generated during the preparation process. Under the action of an external alternating electromagnetic field, they can induce dipole polarization.

[0065] (2) There are a large number of non-uniform heterogeneous interfaces inside the xAlCl3-yMGIC powder, where space charge accumulation can occur. When an external alternating electromagnetic field is applied, interfacial polarization is induced.

[0066] (3) The special three-dimensional porous layered structure of xAlCl3-yMGIC powder allows the graphite layers to easily interlock with each other, forming an interconnected and structurally complete conductive network, thus causing conduction loss;

[0067] (4) xAlCl3-yMGIC powder contains trace oxides derived from MG, which can provide a certain degree of dielectric loss and magnetic loss (such as Al2O3, Fe2O3, MgO and CaO, etc.), optimize the material's wave transmission, and improve the material's impedance matching characteristics (such as SiO2, MnO2 and TiO2, etc.);

[0068] (5) There are a large number of three-dimensional layered structures inside the xAlCl3-yMGIC powder. The incident electromagnetic wave can be reflected and scattered multiple times between the layers, which prolongs the propagation path and propagation time, amplifies the effects of dielectric loss and magnetic loss, and enhances the electromagnetic wave attenuation ability of the product.

[0069] The present invention also provides an expanded microcrystalline graphite, which is obtained by subjecting the above-mentioned microcrystalline graphite intercalation compound to high-temperature expansion treatment.

[0070] Wherein, the temperature of the high temperature puffing treatment is 800-1000°C, which can be 800, 850, 900, 950, 1000, or any value between 800 and 1000°C, and the time is 40-100s, which can be 40, 50, 60, 70, 80, 90, 100, or any value between 40 and 100s.

[0071] See also Figure 1 , Figure 1 Schematic diagram of the preparation process of xAlCl3-yMGIC and EMG powders.

[0072] In the present invention, EG is usually prepared by rapidly heating GICs at high temperature, and the basic principle of its high-temperature expansion is actually the process of gasification or decomposition of compounds inserted between graphite layers.

[0073] In the present invention, AlCl3-MGIC powder is quickly placed in a high-temperature tube furnace, and the AlCl3-MGIC powder will reach a high temperature state in an instant. At this time, the AlCl3 molecules that play a supporting role between the graphite layers will be gasified again, converted into AlCl3 vapor, and escape from the gaps between the graphite layers. However, the escape process may not be smooth, and may be hindered by the graphite layer, so that the MG is squeezed in a direction perpendicular to the graphite layer, thereby generating an expansion effect in the axial direction. In addition, a large number of lamellar ordered areas existing in the graphite will be impacted by the AlCl3 vapor formed by cracking, thereby generating a large number of lamellar voids.

[0074] The present invention also provides an application of the above-mentioned microcrystalline graphite intercalation compound in the preparation of electromagnetic wave absorbing or shielding materials.

[0075] The present invention also provides a use of the expanded microcrystalline graphite in preparing electromagnetic wave absorbing or shielding materials.

[0076] This paper adopts high-temperature mechanochemical method, uses anhydrous AlCl3 as intercalation agent to intercalate MG, explores the influence of AlCl3 content on the organizational structure, electromagnetic parameters and wave absorption performance of xAlCl3-yMGIC powder, and analyzes its formation mechanism and wave absorption mechanism; on this basis, the high-temperature puffing method is used to expand the xAlCl3-yMGIC powder to obtain EMG powder, and its organizational structure, electromagnetic parameters and wave absorption performance are studied. The main conclusions are as follows:

[0077] (1) The AlCl3 content has a significant effect on the microstructure, electromagnetic parameters and wave absorption performance of the xAlCl3-yMGIC powder. When x=y=1, the product has a distinct layered structure and better wave absorption performance. Its minimum reflection loss reaches -37.6dB when the matching thickness is 1.6mm, while the minimum reflection loss of the original MG is only -2.0dB. The wave absorption performance of the product has been significantly improved.

[0078] (2) Using AlCl3-MGIC powder as raw material, EMG powder can be successfully prepared by high-temperature expansion method. The product has an enlarged interlayer spacing and a large number of pore structures, which makes its conductive network more complete and increases the dielectric loss capacity. However, the excessive dielectric constant leads to impedance matching imbalance, and the minimum reflection loss of EMG powder is reduced to -2.3dB.

[0079] (3) The formation process of xAlCl3-yMGIC powder can be divided into four stages, namely, the gasification of AlCl3 and the pyrolysis of C4H4ClNO2, the activation stage of gas phase AlCl3 breaking through the energy barrier between MG layers, the diffusion stage of AlCl3 molecules in the MG carbon atom layer, and the bonding stage of forming certain chemical bonds between AlCl3 and carbon atoms. The formation process of EMG powder is that under the action of instantaneous high temperature, the gasification and escape of AlCl3 molecules causes MG to be squeezed upward along the C-axis direction perpendicular to the graphite sheet, thus producing an expansion effect.

[0080] (4) The wave absorption mechanism of xAlCl3-yMGIC powder can be attributed to its good dielectric loss capacity, including dipole polarization, interface polarization and conduction loss; at the same time, the trace amount of dual-complex dielectric oxides (such as Al2O3, Fe2O3, MgO and CaO, etc.) contained in the product may also provide a certain magnetic loss. Both xAlCl3-yMGIC and EMG powders have introduced a complete conductive network and an obvious multilayer structure, which is conducive to the multiple reflection and scattering of the incident electromagnetic wave in the powder, amplifying the effect of dielectric loss and magnetic loss.

[0081] In order to further understand the present invention, the microcrystalline graphite intercalation compound and expanded microcrystalline graphite provided by the present invention and their applications are described below in conjunction with the embodiments. The protection scope of the present invention is not limited by the following embodiments.

[0082] Example

[0083] 1. Experimental materials and equipment

[0084] The raw materials and reagents used in the sample preparation process are shown in Table 1.

[0085] Table 1 Experimental materials and reagents

[0086]

[0087] The equipment used in the examples and the instruments used to characterize the samples are shown in Table 2.

[0088] Table 2 Experimental equipment and instruments

[0089]

[0090]

[0091] 2. Preparation of xAlCl3-yMGIC powder and EMG powder

[0092] The specific preparation process of xAlCl3-yMGIC powder is as follows:

[0093] Weigh 10g of N-chlorosuccinimide as a chlorinating agent, then evenly mix anhydrous AlCl3 and MG with the chlorinating agent according to m(AlCl3):m(MG)=3:1(3AlCl3-MGIC), 1:1(AlCl3-MGIC) and 1:3(AlCl3-3MGIC) (keep the total mass of the mixed powder at 100g). The ball milling temperature is 523K, the ball milling time is 10h, and the ball-to-material ratio is 20:1. Add 10ml of concentrated hydrochloric acid (12mol·L -1 ) was added to 500 mL of deionized water to prepare a mixed solution, and then the product was slowly added to the mixed solution and magnetically stirred for 30 min for acid washing to remove the unreacted intercalation agent AlCl3. Finally, the acid-washed product was repeatedly washed with deionized water and anhydrous ethanol and dried for 6 h.

[0094] The EMG powder was prepared by treating xAlCl3-yMGIC powder with a high temperature expansion method. The specific preparation process is as follows: the tube furnace is heated to 1173K, and after the furnace temperature stabilizes, the porcelain boat containing xAlCl3-yMGIC powder is quickly placed in the tube furnace, and the reaction is carried out at a constant temperature for 60 seconds before being taken out. The schematic diagram of the preparation process is shown in the figure. Figure 1 .

[0095] 3. Performance test of xAlCl3-yMGIC powder

[0096] (1) The samples were analyzed for phase and crystal structure using an X-ray diffraction analyzer (XRD, Cu target Kα radiation, scanning rate 5° / min, scanning angle 10°-80°); the results are shown in Figure 2 , Figure 2 The XRD patterns of MG and xAlCl3-yMGIC powders. With the compounding of MG and AlCl3, several samples showed new characteristic peaks at about 2θ=27.5°, corresponding to the (00l) crystal plane of GICs, and the higher the AlCl3 content, the greater the intensity of the characteristic peak. In addition, the characteristic peak of 3AlCl3-MGIC at 2θ=27.5° broadened, indicating that its degree of crystallization decreased, which may be due to the fact that the excess AlCl3 affected the strength of the grinding ball on MG, which had an adverse effect on the exfoliation of MG, thereby hindering the intercalation process.

[0097] (2) Using Fourier transform infrared spectrometer (FT-IR, wavelength range 400cm -1 -4000cm -1 ) was used to characterize the material composition of the samples. The results are shown in Figure 3 , Figure 3 FT-IR spectra of MG and xAlCl3-yMGIC powders. -1 and 1630cm -1The characteristic peaks at 1160 cm-1 and 1160 cm-2 correspond to the stretching vibrations of CO and C=O, respectively. The O element may come from the decomposition of the chlorinating agent. -1 and 1680cm -1 The characteristic peaks at 1200-1430 cm-1 correspond to the C-C and C=C bonds in the product C lattice, indicating that the C structure has strong stability before and after the reaction. -1 and 3100cm -1 The characteristic peaks at 1630 cm-1 and 1640 cm-2 correspond to the CH bonds and NH bonds in the residual chlorinating agent. -1 The characteristic peak at 2900 cm-1 corresponds to the CN bond, indicating that the N atom in the chlorinating agent has a certain bonding effect with the C atom in MG. -1 The characteristic peak at 3400 cm corresponds to the OH bond in the adsorbed water molecule. -1 The characteristic peak at corresponds to the -OH functional group on the sample surface. In summary, there are a large number of polar functional groups and chemical bonds on the sample surface, which will show different attraction and binding abilities to the free electrons inside the material. Under the action of the external alternating electromagnetic field, dipole polarization will be generated and electromagnetic waves will be attenuated.

[0098] (3) The composition of MG and its derivatives was characterized by X-ray fluorescence (XRF) (Rh target Kα radiation, wave number range 7000 cm -1 -350cm -1 ). The results are shown in Table 3, which shows the XRF analysis results of MG and xAlCl3-yMGIC powders. In general, XRF tests mainly characterize the content of oxides in samples. Since AlCl3 exists in the samples of this study, AlCl3 is converted into Al2O3 by burning during the test for characterization. The original microcrystalline graphite MG is mainly composed of C (about 83.23 mass%), oxides (Al2O3, SiO2 and Fe2O3, etc., about 15.66 mass%), volatiles and water (about 1.06 mass%) and trace chlorine elements (chloride about 0.05 mass%). Compared with the original MG, the material composition of the xAlCl3-yMGIC powder remains unchanged, but some contents have changed. Among them, the C content is reduced, the content of Al2O3 and chlorine elements is significantly increased, and the more AlCl3 is added, the greater the increase.

[0099] Table 3 Composition analysis of MG and xAlCl3-yMGIC powders

[0100]

[0101] (4) The specific surface area, pore size distribution and pore volume of the samples were characterized by using a specific surface area and pore size analyzer (BET, test temperature was 77K, degassing temperature and degassing time were 423K and 8h respectively). The structure of the product will change with the change of intercalation conditions, thereby affecting the specific surface area and pore size distribution of the product. In the relative pressure (P / P0) range of 0-1, the specific surface area and pore structure of MG and xAlCl3-yMGIC powders were analyzed by N2 adsorption-desorption curves, and related calculations were performed, such as Figure 4 , Figure 5 and Figure 6 .

[0102] Figure 4 is the N2 adsorption-desorption isotherms of MG and xAlCl3-yMGIC powders, Figure 4 The results show that the N2 adsorption-desorption curves of all samples are typical IV-type curves. When P / P0<0.04, the adsorption / desorption of several samples show an upward trend. When 0.4<P / P0<1.0, the xAlCl3-yMGIC powder has an obvious H3-type hysteresis loop, indicating that there are both microporous and mesoporous structures in the sample.

[0103] The specific surface area, pore volume and average pore size distribution of several samples were calculated by BET method, such as Figure 5 As shown, Figure 5 is the BET parameter distribution curve of MG and xAlCl3-yMGIC powder. Figure 5 It can be seen that MG has a smaller specific surface area, pore volume and average pore size. After intercalation treatment, the specific surface area, pore volume and average pore size of xAlCl3-yMGIC powder increased, reaching the maximum when m(AlCl3):m(MG)=1:1, indicating that the intercalation reaction was relatively complete at this time and the intercalation effect was better.

[0104] The pore size distribution of the samples was further analyzed by the BJH method, such as Figure 6 As shown, Figure 6 The pore size distribution diagram of MG and xAlCl3-yMGIC powders. Figure 6It can be seen that MG is mainly distributed in micropores. After intercalation treatment, the pore size of the product increases, and it also shows micropore distribution, mesopore distribution and a small amount of macropore distribution. Under the synergistic effect of high temperature and mechanical force, the edges of the large graphite flake structure are destroyed and peeled off into multiple small-sized graphite flakes. AlCl3 vapor enters between the graphite layers, thereby increasing the specific surface area, pore size and pore volume of the graphite. Therefore, the xAlCl3-yMGIC powder has a high specific surface area and rich pore structure. According to the Maxwell-Garnett theory, an appropriate specific surface area is conducive to improving impedance matching and interface polarization. The porous structure is conducive to reducing the material density, providing abundant interfaces and active sites, and further promoting interface polarization and multiple reflections and scattering of electromagnetic waves.

[0105] (5) Raman spectroscopy was used to characterize the graphitization degree and defect degree of the material (room temperature, excitation light source of 514 nm, wave number range of 200 cm -1 -4000cm -1 ), the results are shown in Figure 7 , Figure 7 The Raman patterns of MG and xAlCl3-yMGIC powders. -1 The D peak at 1578 cm represents the degree of defect in the carbon atom lattice. -1 The G peak at corresponds to the sp 2 The in-plane stretching vibration of hybrid carbon atoms reflects the degree of graphitization of carbon materials. Therefore, the intensity ratio of D peak to G peak (I D / I G ) is used to characterize the degree of defects in graphite in the sample. D / I G The larger the value, the greater the degree of defect.

[0106] Under the action of an external alternating electromagnetic field, the defects in graphite can act as polarization centers to produce polarization relaxation and loss of electromagnetic waves. D / I G The values ​​are 0.132, 0.347, 1.334 and 0.814 respectively. It can be seen that with the increase of AlCl3 content, I D / I G It increases first and then decreases. This is because the gas phase AlCl3 can penetrate the graphite layer to generate graphite interlayer compounds, which effectively increases the graphite interlayer spacing and reduces the graphite sp 2The planar size of the structure increases the lattice defect density inside the product. When the AlCl3 content is too high, on the one hand, it will hinder the interaction between the grinding balls and MG, and on the other hand, the excess AlCl3 will aggregate with each other, causing the graphite sheets to adhere to each other and block, reducing the effect of mechanical force, thereby reducing the defect density of the xAlCl3-yMGIC powder.

[0107] (6) The elemental composition and chemical state of the samples were characterized by X-ray photoelectron spectroscopy (XPS). Figure 8 , Figure 8 The XPS total spectra and high-resolution spectra of the corresponding elements of MG and AlCl3-MGIC powders.

[0108] Figure 8 (a) is the full XPS spectra of MG and AlCl3-MGIC powders. In the spectrum of MG, only the absorption peaks of C1s and O1s can be observed, indicating the presence of C and O elements in MG. The spectrum of AlCl3-MGIC powder contains absorption peaks of C1s, O 1s, N 1s, Cl 2p and Al 2p, proving the presence of these elements, among which O and N elements come from the residual chlorinating agent.

[0109] Figure 8 The C1s high-resolution spectrum of MG in (b) can be fitted into two characteristic peaks, which correspond to CC / C=C bond and COC bond in graphite at binding energies of about 284.8eV and 285.5eV, respectively. The C1s high-resolution spectrum of AlCl3-MGIC powder can be fitted into four characteristic peaks. The characteristic peak at a binding energy of about 284.8eV corresponds to CC / C=C / CH bond, which has the highest intensity among the four characteristic peaks, indicating that the graphite structure remains stable before and after the reaction; the characteristic peaks at 285.6eV and 286.8eV correspond to COC bond and OC=O / CN bond, respectively, where O atoms and N atoms may come from the thermal decomposition of the chlorinating agent; the characteristic peak at 288.8eV corresponds to C-Cl bond, which comes from the bonding between AlCl3 and graphite under the combined action of chlorine and high temperature, and also indicates that the Cl atoms in AlCl3 are closer to the C atomic layer than Al atoms.

[0110] N1s high resolution spectrum of AlCl3-MGIC powder ( Figure 8 (c)) can be fitted into two characteristic peaks. The characteristic peaks at binding energies of about 400.5 eV and 402.2 eV correspond to NH bonds and CN bonds, respectively, both of which are derived from residual chlorinating agents. At the same time, in the high-resolution spectra of O1s of MG and AlCl3-MGIC powders ( Figure 8(d)), there are characteristic peaks of OC=O and CO at binding energies of about 531.8eV and 533.1eV, respectively, which are derived from the products formed by the O atoms in the chlorinating agent and the C atoms in the graphite under high temperature.

[0111] High-resolution Al 2p spectrum of AlCl3-MGIC powder ( Figure 8 (e)) There is a very strong characteristic peak at a binding energy of about 75.1 eV, which corresponds to the characteristic peak of the Al element in AlCl3. High-resolution spectrum of Cl 2p of AlCl3-MGIC powder ( Figure 8 There are four different chemical states of Cl atoms in (f). The characteristic peaks at binding energies of about 198.5 eV and 200.3 eV correspond to the Cl 2p 3 / 2 and Cl 2p 1 / 2 The characteristic peaks at the binding energies of about 201.8 eV and 202.8 eV correspond to the 2p 3 / 2 and 2p 1 / 2 Electron orbits.

[0112] Combined with the bonding state of C, Cl and Al elements in XPS, it can be considered that the existence form of AlCl3 between graphite layers is C-AlCl3-C, and the chemical bond arrangement order is C-Cl-Al-Cl-C. In addition, there are a large number of functional groups and chemical bonds in the xAlCl3-yMGIC powder. Under the action of the external alternating electromagnetic field, they can interact with the incident electromagnetic waves and consume the electromagnetic waves.

[0113] (7) Scanning electron microscope (SEM), transmission electron microscope (TEM) and X-ray energy dispersive spectroscopy (EDS) analysis system were used to observe the particle size distribution, morphology and element distribution of the samples; the results are shown in Fig. 9 , Fig. 9 FE-SEM morphology images, EDS element surface distribution images, TEM images and HR-TEM images of MG and xAlCl3-yMGIC powders.

[0114] Depend on Fig. 9 (a) It can be seen that MG is an irregular flake structure with no obvious stratification. The size distribution is uneven, ranging from a few microns to more than ten microns.

[0115] Fig. 9(bd) are the morphology of the products after different contents of AlCl3 and MG are composited. Due to the continuous mechanical force during the reaction, the diameter of the graphite flakes of the xAlCl3-yMGIC powder is reduced, and the graphite flakes are significantly expanded, with a more obvious parallel structure and stratification phenomenon. At the same time, the graphite layer also produces a certain degree of wrinkles, and the distance between the graphite layers increases with slight peeling and accumulation. With the increase of AlCl3 content, the number of layered structures of the product increases first and then decreases. Among them, the graphite layer structure of the product is the richest when m(AlCl3):m(MG)=1:1. This may be because as the AlCl3 content increases, more AlCl3 vapor is inserted between the graphite flakes to form xAlCl3-yMGIC. In contrast, excessive AlCl3 may limit the effect of the grinding ball on MG, reduce the degree of graphite layer edge fragmentation, reduce the AlCl3 intercalation rate, and reduce the number of layered structures.

[0116] Fig. 9 (ef) is the EDS element distribution map of AlCl3-MGIC powder. Al and Cl elements are evenly distributed between C elements, indicating that AlCl3 has successfully entered between graphite sheets.

[0117] Fig. 9 (g) is the TEM image of MG. MG presents a large flake structure with a size distribution of several microns to tens of microns, which is consistent with the size information obtained from the SEM image. HR-TEM image ( Fig. 9 (h) shows that the lattice spacing of the (002) plane of C in MG is 0.338 nm, and the corresponding SAED pattern ( Fig. 9 The inset in (h) shows that it has a typical polycrystalline structure.

[0118] Fig. 9 (i) is the TEM image of AlCl3-MGIC powder. AlCl3-MGIC powder presents a multilayer structure, with certain wrinkles and clear pore structures on the graphite sheets.

[0119] Fig. 9 (j) is the HR-TEM image of AlCl3-MGIC powder. The lattice spacing of the (002) crystal plane of the internal C is 0.356nm, which is significantly larger than that of MG, indicating that AlCl3 is successfully inserted into the C lattice of MG. The corresponding SAED illustration shows that the C in the AlCl3-MGIC powder is still a typical polycrystalline structure, indicating that the C crystal form remains highly stable before and after intercalation. In addition, the presence of lattice defects is also observed in the HR-TEM image. The large amount of lattice distortion and structural defects in the AlCl3-MGIC layer can not only provide rich heterogeneous interfaces, but also increase electron transfer channels, which helps to enhance the interface polarization loss and conduction loss, thereby improving the material's microwave absorption performance.

[0120] (8) A vector network analyzer (VNA) was used to test the electromagnetic parameters (ε', ε", μ', μ") of the sample in the frequency range of 2-18 GHz. Matlab software was then used to calculate the three-dimensional reflection loss diagram of the sample and the reflection loss value (R L ), C0 value, attenuation coefficient (α) and impedance matching coefficient (Z) curve. Figures 10-12 , Fig.10 This is the relationship curve between the electromagnetic parameters and frequency of MG and xAlCl3-yMGIC powders. Fig.11 3D R of MG and xAlCl3-yMGIC powders L Figure and R in a specific thickness range L curve. Fig.12 Cole-Cole curves of MG and xAlCl3-yMGIC powders.

[0121] Fig.10 (ab) are the ε' and ε" of MG and xAlCl3-yMGIC powders. The ε' and ε" values ​​of MG are both relatively low, fluctuating between about 2.6 and 0, respectively, indicating that although MG has a certain dielectric storage capacity, its dielectric loss capacity is extremely weak. The ε' and ε" values ​​of xAlCl3-yMGIC powder have been significantly improved, and the AlCl3 content has a significant effect on the ε' and ε" values. With the increase of AlCl3 content, the ε' and ε" values ​​of the product first increase and then decrease. Among them, AlCl3-MGIC powder has the largest ε' and ε" values, fluctuating between about 22-33 and 1.5-13, respectively, indicating that it has better dielectric loss capacity. The defect density, specific surface area and porosity inside the AlCl3-MGIC powder are higher than those of other samples. The large number of pores can produce enough non-uniform "solid-gas interfaces". In addition, there are abundant heterogeneous interfaces between the oxide / graphite layer, graphite layer / graphite layer, and graphite layer / AlCl3 components inside MG. The space charges accumulated on these interfaces can produce interface polarization under the action of an external alternating electromagnetic field, thereby improving the dielectric loss capacity. However, excessive AlCl3 will cause AlCl3 to agglomerate and accumulate between graphite sheets, reducing the number of effective interfaces, hindering the migration of carriers on the heterogeneous interface, and is not conducive to the generation of interface polarization.

[0122] In addition to interfacial polarization, dipole polarization also plays an important role. In the present invention, a large number of defects and vacancies between the layer structures of the product can induce dipole polarization. The occurrence of these polarization phenomena not only helps to consume electromagnetic waves, but also the generated polarized charges also make an important contribution to improving the complex dielectric constant of the product. In addition, the layers of xAlCl3-yMGIC powder are more likely to interlock with each other to form an interconnected conductive network, which promotes the directional migration of free electrons and enhances the effect of conduction loss.

[0123] Fig.10 (cd) are μ' and μ" of MG and xAlCl3-yMGIC powders. Since both MG and AlCl3 in the present invention are non-magnetic components, μ' and μ" of xAlCl3-yMGIC powder fluctuate around 1 and 0, respectively.

[0124] Fig.10 (ef) is tanδe and tanδm of MG and xAlCl3-yMGIC powders. In the whole frequency range, tanδe>tanδm exists for all xAlCl3-yMGIC powders, so the electromagnetic wave loss mechanism is mainly dielectric loss. Fig.10 (b) and Fig.10 (e), the curves of ε" and tanδe of the samples have similar changing trends and multiple resonance peaks can be observed, indicating that during the electromagnetic wave loss process, xAlCl3-yMGIC powder has multiple polarization relaxation processes.

[0125] Fig.11 3D R of MG and xAlCl3-yMGIC powders L Figure and R in a specific thickness range L The frequency dependence curve of Fig.11 (a1-a2) shows that the R Lmin The R of xAlCl3-yMGIC powder is only -2.0dB, indicating that it has almost no electromagnetic wave absorption effect. L With the increase of AlCl3 addition, the R Lmin It increases first and then decreases, reaching the highest value when m(AlCl3):m(MG)=1:1, R Lmin When the frequency is 9.52 GHz, it is -37.6 dB (the electromagnetic wave absorption rate is 99.9826%), and the corresponding matching thickness is 1.6 mm. At this time, the sample has the best wave absorption performance.

[0126] Depend on Fig.11 (a2-d2) It can be seen that with the change of matching thickness, the R LThe R of AlCl3-3MGIC and 3AlCl3-MGIC powders is consistently lower. Lmin All of them move toward the low frequency direction, which indicates that after the matching thickness increases, they have better absorbing effect at low frequency. AlCl3-MGIC powder has effective absorption peaks at both high and low frequencies, indicating that it has good absorbing effect in the high and low frequency ranges. In summary, the absorbing effect that meets specific needs can be obtained by changing the AlCl3 content and the matching thickness of xAlCl3-yMGIC powder, and AlCl3-MGIC powder has the best matching thickness and R in all samples. L , showing excellent wave absorbing performance.

[0127] Fig.12 The Cole-Cole curves of MG and xAlCl3-yMGIC powders. The Cole curve of MG shows a chaotic state, and the ε" value is distributed in the range of 0.01-0.08, indicating that its polarization relaxation process is weak. The ε" values ​​of xAlCl3-yMGIC powders are distributed in the range of 2.0-2.8, 1.0-14 and 1.0-1.6, respectively, indicating that with the increase of AlCl3 content, the dielectric loss capacity of the product first increases and then weakens, and is stronger than that of MG. The curves of xAlCl3-yMGIC powders are all irregular shapes composed of multiple Cole semicircles and straight line "tails", indicating that their dielectric loss is composed of multiple polarization relaxation and conduction loss. Specifically, under the action of an external electromagnetic field, a large number of defects and vacancies generated during high-temperature mechanochemical action and intercalation reaction can serve as polarization centers, resulting in polarization relaxation and thus loss of electromagnetic waves. According to the XPS and FT-IR analysis mentioned above, there are abundant polar functional groups and chemical bonds in the product, which have different attraction and binding abilities for free electrons inside the material, thereby generating electron pair differences, which can induce dipole polarization under the action of an external alternating electromagnetic field. There are a large number of inhomogeneous "gas-solid" interfaces, oxide / C interfaces, C / C interfaces, and AlCl3 / C interfaces inside the product. The "Schottky barriers" formed at these interfaces can cause charge redistribution and form spatial charge accumulation. When an external alternating electromagnetic field is applied, the positive and negative charges at these interfaces are forced to rearrange to form a local dipole electric field, thereby generating local microcurrents. At this time, the local microcurrents can interact with the incident electromagnetic waves through the polarization mechanism, thereby converting the electromagnetic waves into other forms of energy (such as heat energy), which enhances dielectric loss.

[0128] In addition to polarization loss, the conduction loss inside the product cannot be ignored. xAlCl3-yMGIC powder has a special porous layered structure, and the layers can easily interlock with each other to form an interconnected conductive network structure. When electromagnetic waves are incident, the free electrons inside the powder can absorb electromagnetic energy and migrate in the surface / interlayer channels of xAlCl3-yMGIC, thereby generating microcurrents to consume electromagnetic energy.

[0129] (9) The static magnetic properties of the samples at 300K were tested using a vibrating sample magnetometer (magnetic field range: -30-30 kOe). Although the μ' and μ" of MG and xAlCl3-yMGIC powders are low, there may still be a certain amount of magnetic loss due to the presence of trace amounts of dual complex media with both magnetic loss and dielectric loss, such as Al2O3, Fe2O3, MgO and CaO in the powders. It is necessary to discuss the magnetic loss mechanism. The test results are shown in Figures 13-14 , Fig.13 C0-f curves of MG and xAlCl3-yMGIC powders. Fig.13 It can be seen that within 2-18 GHz, the C0 values ​​of MG, AlCl3-3MGIC and 3AlCl3-MGIC powders all show a trend of decreasing or fluctuating with increasing frequency, indicating that their magnetic loss mechanism is mainly natural resonance; the C0 value of AlCl3-MGIC powder remains basically stable, indicating that eddy current loss is its main magnetic loss mechanism.

[0130] Fig.14 The attenuation coefficient (α) and impedance matching characteristics (Z) of MG and xAlCl3-yMGIC powders vary with frequency. Fig.14 (a) is the curve of α changing with frequency for MG and xAlCl3-yMGIC powders. As the frequency increases, the α value of MG basically fluctuates around 0, indicating that MG has basically no microwave attenuation ability. The α values ​​of AlCl3-3MGIC and 3AlCl3-MGIC powders both increase with increasing frequency, indicating that these two samples have stronger attenuation capabilities for electromagnetic waves at high frequencies. For AlCl3-MGIC powder, its α value increases with increasing frequency in the range of 2-10GHz, but decreases with increasing frequency in the range of 10-18GHz, indicating that the attenuation capability of AlCl3-MGIC powder in the low frequency range is stronger than that in the high frequency range, and at the same time, it is stronger than the attenuation capability of AlCl3-3MGIC and 3AlCl3-MGIC powders.

[0131] Fig.14(b) is the curve of Z changing with frequency for MG and xAlCl3-yMGIC powders. Compared with MG, the impedance matching characteristics of xAlCl3-yMGIC powders are significantly improved. This change can be explained from two aspects: first, the introduction of N atoms can significantly improve the impedance matching characteristics of carbon materials without the introduction of magnetic particles.

[0132] In the present invention, N atoms in the chlorinating agent interact with C atoms in MG under the action of high temperature and mechanical force to form CN bonds, thereby introducing N atoms into the product; secondly, trace Al2O3, Fe2O3, MgO and CaO in MG and xAlCl3-yMGIC powder can provide dielectric loss and magnetic loss. At the same time, SiO2, MnO2 and TiO2 also have excellent wave transmission. The synergistic effect of dielectric loss and magnetic loss and the enhancement of material wave transmission are helpful to optimize the impedance matching characteristics between the material and free space. Compared with other samples, the Z value of AlCl3-MGIC powder is closer to 1 within 8.5-10GHz, indicating that its impedance matching characteristics are better.

[0133] 4. EMG performance test

[0134] (1) The samples were analyzed for phase and crystal structure using an X-ray diffraction analyzer (XRD, Cu target Kα ray, scanning rate 5° / min, scanning angle 10°-80°). The results are shown in Fig.17 . Fig.17 The XRD diagrams of MG, AlCl3-MGIC powder and EMG powder are shown in Figure 2. After the AlCl3-MGIC powder was subjected to high-temperature expansion treatment, the characteristic peak of the (001) crystal plane of GICs located at about 2θ=27.5° disappeared. This is because the AlCl3 inside the AlCl3-MGIC powder was vaporized and escaped again due to the instantaneous high-temperature expansion treatment. The characteristic peak at the (002) crystal plane of the obtained EMG showed a trend of moving to a lower angle compared to the MG and AlCl3-MGIC powders, indicating that the diffraction angle θ decreased, resulting in an increase in the interplanar spacing d, which can be attributed to the vaporization and escape of AlCl3 inside the AlCl3-MGIC powder, resulting in an increase in the interlayer spacing of graphite.

[0135] (2) The specific surface area, pore size distribution and pore volume of the samples were characterized by using a specific surface area and pore size analyzer (BET, test temperature was 77 K, degassing temperature and degassing time were 423 K and 8 h, respectively).

[0136] In the relative pressure (P / P0) range of 0-1, the specific surface area and pore structure of EMG powder were analyzed by N2 adsorption-desorption curves, and related calculations were performed, such as Fig.18 shown.

[0137] Depend on Fig.18 (a) It can be seen that the EMG powder curve is a typical IV type curve. When P / P0<0.04, its adsorption / desorption amount shows an upward trend. When 0.4<P / P0<1.0, it shows an obvious H3 type hysteresis loop, indicating that both mesoporous and macroporous structures exist in EMG. The pore size distribution of EMG is further analyzed according to the BJH method, as shown in Figure 2. Fig.18 (b) The results show that EMG contains macropores and a small amount of mesopores. Compared with the BET analysis of AlCl3-MGIC powder, the pore size of EMG powder is larger than that of AlCl3-MGIC powder, which can be attributed to the gasification and escape of AlCl3.

[0138] (3) The elemental composition and chemical state of the samples were characterized by X-ray photoelectron spectroscopy (XPS). Figures 19-20 , Fig.19 The XPS spectra of EMG and AlCl3-MGIC powders are shown in Figure 2. The characteristic peaks of N1s, Cl 2p and Al2p in EMG powder disappear, indicating that high-temperature expansion can make AlCl3 in AlCl3-MGIC powder escape and form EMG, thus proving the formation of EMG.

[0139] Fig. 20 High-resolution elemental spectra of C1s and O1s of EMG powder. Fig. 20 (a) is the high-resolution spectrum of C1s, with characteristic peaks at binding energies of about 284.8 eV, 285.7 eV, and 289.6 eV, corresponding to graphene sp 2 The C=C / CC bonds, COC bonds and OC=O bonds caused by hybrid carbon atoms indicate that there are oxygen-containing functional groups on the surface of the EMG powder. Among them, the characteristic peak at the C=C / CC bond has the largest peak intensity, indicating that the EMG powder still maintains the stability of the basic graphite structure after expansion. Fig. 20 (b) is the elemental high-resolution spectrum of O1s. The characteristic peaks at binding energies of approximately 531.7 eV and 533.0 eV correspond to the OC=O bond and COC bond, respectively.

[0140] (4) In order to observe the volume changes of MG, EMG and AlCl3-MGIC powders, 1.0 g of each sample was placed in a beaker of the same range, as shown in Fig.21 , Fig.21 The volume change diagram of MG, AlCl3-MGIC and EMG powders of equal mass. Compared with MG, the volume of the products after intercalation (AlCl3-MGIC powder) and expansion (EMG powder) is significantly increased, especially EMG, whose volume expands nearly 20 times, indicating that this study successfully prepared MG into EMG.

[0141] (5) Scanning electron microscope (SEM) and transmission electron microscope (TEM) analysis systems are used to observe the particle size distribution, morphology, and element distribution of the samples;

[0142] SEM analysis of MG, xAlCl3-yMGIC and EMG powders was performed, as shown in Fig. 22 As shown. EMG presents a typical "worm-like" structure, about 100μm long and 40μm wide. Compared with AlCl3-MGIC powder, the interlayer spacing of EMG is significantly increased, and the entire structure appears looser and fluffier. This is because after the AlCl3-MGIC powder is instantly placed in a high-temperature environment, the AlCl3 between the graphite sheets vaporizes and escapes, causing the interlayer van der Waals force to be destroyed. In addition, there are a large number of microcells composed of thin sheets on the surface of EMG, with a size of 1-5μm. The spacing between these sheets is submicron, and each sheet may be composed of many graphene-level sheets. There are obvious wrinkles on the surface of the graphite sheet, and a large number of two-dimensional thin-layer graphite sheets are interconnected to form a three-dimensional honeycomb mesh porous structure.

[0143] Fig.23 TEM and HRTEM images of EMG powder. Fig.23 (ab) shows that EMG has an obvious multilayer structure, and there are a large number of holes and wrinkles on the graphene sheet, indicating that EMG has porosity and high specific surface area. In addition, Fig.23 (cd) It can also be observed that there are lattice defects in EMG, which may be introduced by mechanical force during high temperature mechanical force. Selected area electron diffraction shows that EMG is a single crystal structure, and the (002) crystal plane spacing of C is about 0.364nm.

[0144] (6) A vector network analyzer (VNA) was used to test the electromagnetic parameters (ε', ε", μ', μ") of the sample in the frequency range of 2-18 GHz. Matlab software was then used to calculate the three-dimensional reflection loss diagram of the sample and the reflection loss value (R L ). The results are shown in Figure 24-25 .

[0145] Fig.24 Graph showing the relationship between electromagnetic parameters and frequency for MG, AlCl3-MGIC and EMG powders.

[0146] in, Fig.24(ab) are ε' and ε" of MG, EMG and AlCl3-MGIC powders. Compared with MG and AlCl3-MGIC powders, the ε' and ε" values ​​of EMG powder are significantly increased, fluctuating in the range of about 260.8-113.0 and about 661.9-101.7, respectively. This indicates that after the expansion treatment, the dielectric properties of the product are significantly improved. This change can be attributed to the change in the product structure. Among the three, EMG has the richest three-dimensional layered structure and porous structure. This structure can cause multiple reflections and scattering of the incident electromagnetic wave inside the material, extending the transmission path and propagation time of the electromagnetic wave, and amplifying the effect of dielectric loss. In addition, this structure is also conducive to the integrity of the conductive network inside the material, thereby amplifying the effect of conduction loss.

[0147] Fig.24 (cd) are μ' and μ" of MG, EMG and AlCl3-MGIC powders. The μ' and μ" of the three are not much different, all fluctuating around 1.03 and in the range of 0-0.04, which indicates that the intercalation and expansion treatments have little effect on the magnetic loss capacity of MG, and all three products show weak magnetic loss capacity.

[0148] Fig.24 (ef) is tanδe and tanδm of MG, EMG and AlCl3-MGIC powders. The tanδe of MG, EMG and AlCl3-MGIC powders fluctuate around 0, 1.0-2.5 and 0.2-0.4, respectively. Therefore, EMG has the strongest dielectric loss capacity among the three, which is consistent with Fig.24 (ab) The analysis results of ε' and ε" are consistent. The tanδm of the three powders fluctuates in the range of 0-0.03, indicating that the magnetic loss capacity of the three is poor, which is consistent with Fig.24 (cd) The analysis results for μ' and μ" are consistent. In addition, in the entire frequency range, the tanδe values ​​of EMG and AlCl3-MGIC powders are much larger than their tanδm values, indicating that their loss mechanism is mainly dielectric loss; the tanδe value and tanδm value of MG are not much different, and its loss mechanism is the synergistic effect of dielectric loss and magnetic loss, among which the magnetic loss may come from the Al2O3, Fe2O3, MgO and CaO stored inside.

[0149] Fig.25 The three-dimensional R of EMG powder L Graph and three-dimensional Cole-Cole graph. Among them, Fig.25 (a) is the three-dimensional R of EMG L Fig. Comparison of R of MG, AlCl3-MGIC and EMG powders L , their R LminThe value increased from -2.0dB to -37.6dB and then decreased to -2.3dB, indicating that their wave absorption performance first increased and then weakened, and EMG basically had no electromagnetic wave absorption effect. This is because although the three-dimensional layered structure significantly enhanced the dielectric loss capacity of EMG powder, it basically had no magnetic loss capacity, that is, the values ​​of ε' and ε" were much larger than the values ​​of μ' and μ", resulting in an imbalance in impedance matching and the inability to obtain excellent electromagnetic wave attenuation capacity.

[0150] Fig.25 (b) is the three-dimensional Cole-Cole plot of EMG powder. The Cole curve of EMG is an irregular shape consisting of Cole semicircles in the mid- and high-frequency bands and a "straight tail" in the low-frequency band, indicating that its dielectric loss mechanism is composed of dipole polarization relaxation and conduction loss. In addition, there are fewer Cole semicircles in EMG powder and its tail straight line is longer, indicating that conduction loss is dominant in EMG powder. This is because the network skeleton of EMG powder is more complete and therefore has better conductivity. In addition, the dipole polarization phenomenon of EMG powder may be caused by lattice defects under the action of electromagnetic waves.

[0151] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a microcrystalline graphite intercalation compound, characterized in that: The following steps are involved: The microcrystalline graphite intercalation compound is obtained by mixing N-chlorosuccinimide, anhydrous aluminum chloride and microcrystalline graphite, ball milling, washing and drying.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the anhydrous aluminum chloride to the microcrystalline graphite is 3:1 to 1:

3.

3. The preparation method according to claim 1, characterized in that: The usage amount of the N-chlorosuccinimide is 10 wt % to 30 wt % of the total amount of the N-chlorosuccinimide, anhydrous aluminum chloride and microcrystalline graphite.

4. The preparation method according to claim 1, characterized in that: The temperature of the mixed ball milling is 200-400° C., the time is 5-12 hours, and the ball-to-material ratio is 5-20:

1.

5. The preparation method according to claim 1, characterized in that: The washing comprises the following steps: The ball-milled reaction product was pickled with a hydrochloric acid solution and then washed with deionized water and anhydrous ethanol.

6. A microcrystalline graphite intercalation compound prepared by the preparation method according to any one of claims 1 to 5.

7. An expanded microcrystalline graphite, characterized in that: The microcrystalline graphite intercalation compound according to claim 6 is obtained by high-temperature expansion treatment.

8. The expanded microcrystalline graphite according to claim 7, characterized in that: The temperature of the high temperature puffing treatment is 800-1000° C., and the time is 40-100 seconds.

9. Use of the microcrystalline graphite intercalation compound as claimed in claim 6 in the preparation of electromagnetic wave absorbing or shielding materials.

10. Use of the expanded microcrystalline graphite as claimed in claim 7 or 8 in preparing electromagnetic wave absorbing or shielding materials.

Citation Information

Cited By

  • Preparation method of expanded graphite-based composite material based on molten salt intercalation and controllable deintercalation thereof

    CN119841312A

  • A preparation method of an expanded graphite-based composite material based on molten salt intercalation and its controllable deintercalation

    CN119841312B